Research on key areas and maturity evaluation of AI military applications - TAO Rui, YANG Zuyao (Zhihui kongzhi yu fangzhen, 2024)
Starting with the concept, principle and classification of AI technology, this article focuses on the analysis of three main scenarios and eight key directions of AI military applications. It comprehensively uses the maturity evaluation method of technology patent analysis and the Gartner technology maturity curve to evaluate the maturity of eight key directions of AI military applications.